4. Subchronic toxicity study of efcovida powder in experimental animals - Nang, Trinh Dinh; Hai, Nguyen Minh; Huong, Tran Thi Thu; Tuyen, Vo Quang; Quyen, Do Linh; Anh, Pham Thi Van; Loan, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2022)
The purpose of this study was to evaluate the subchronic toxicity of Efcovida powder through oral administration in experimental animals. The subchronic toxicity was studied in Wistar rats with oral doses of 90 mg/kg/day and 270 mg/kg/day in 90 consecutive days based on guidance of the World Health Organization and Organisation for Economic Co-operation and Development. Our result showed that Efcovida powder had no deleterious effect on hematological parameters, hepato-renal functions, macroscopic and microscopic images of livers and kidneys of rats. In conclusion, Efcovida powder did not produce the subchronic toxicity in experimental animals.